Rings of fate [large type] - De la Cruz, Melissa, 1971- (Thorndike Press large print high octane., 2026)
"She's a barmaid who doesn't believe in fairy tales. He's a prince cursed to live one. Aren Bellamore has no interest in being anyone's princess. She's too busy running the Raven's Beak tavern, fending off unwanted marriage proposals, and dreaming of escape. But when a brush with death and a dangerously handsome stranger upend her life, Aren finds herself bound to a bargain that could change everything. Prince Dietan has carried the cursed Rings of Fate--ancient weapons of devastating power--since childhood. The magic is killing him, and the enemies are closing in. To make the journey to reverse his curse, he needs a bride to hide his secrets. Aren wants freedom. Pretending to be his fiancée should give them both what they want. But as their perilous journey pits them against political schemes, monstrous Kilandrar, and a growing attraction neither can deny, the line between make-believe and destiny begins to blur. And the fate of two kingdoms may depend on whether a cynical barmaid and a cursed prince are willing to risk their hearts." --